Molecular docking study and molecular dynamic simulation of human cyclooxygenase-2 (COX-2) with selected eutypoids - Taidi, Loubna; Maurady, Amal; Britel, Mohammed Reda (Journal of biomolecular structure & dynamics, 2022)
Inflammation is a key factor linked to almost all chronic and degenerative diseases implicit with certain levels of pain. In studies, over the past few years, it has been discovered that prostaglandins are the main cause of this inflammation and therefore could be blocked. Although no steroidal medications can be effective, natural compounds may offer a safer and often an effective alternative treatment for pain relief, especially for long-term use. Hence to find out natural anti-inflammatory compounds, we have highlighted five important butenolides that are eutypoid A, B, C, D and E with structure similar to that of rofecoxib, by ADMET and druglikeness analysis, followed by molecular docking with human COX-2 enzyme. Molecular docking studies revealed the importance of hydrophobic and hydrophilic amino acid residues for the stability of the ligands and that eutypoids C and E are the best candidates for the synthetic drugs with binding energy of −10.39 kcal/mol and −9.87 kcal/mol, respectively. The resulting complexes were then subject to 50 ns molecular dynamics (MD) simulation studies with the GROMACS package to analyze the stability of docked protein-ligand complexes and to assess the fluctuation and conformational changes during protein-ligand interaction. From the RMSD, RMSF, number of hydrogen bonds, SASA, PCA and MM/PBSA binding free energy analysis, we have found that out of five selected compounds eutypoid E showed good binding free energy of −174.45 kJ/mol, which is also good in other structural analyses. This compound displayed excellent pharmacological and structural properties to be drug candidates. Communicated by Ramaswamy H. Sarma